New autoantigens in rheumatoid arthritis (RA): screening 8268 protein arrays with sera from patients with RA. Issue 4 (28th October 2008) - Auger, I; Balandraud, N; Rak, J; Lambert, N; Martin, M; Roudier, J
Abstract : Objective: To identify new IgG autoantibodies in sera from patients with rheumatoid arthritis (RA). Methods: We tested serum samples from 19 patients with RA with given human leukocyte antigen (HLA)-DR genotypes, from 7 patients with spondylarthropathy, 2 patients with lupus, 4 patients with systemic sclerosis and 10 healthy individuals on 8268 human protein arrays. Results: We identified four antigens (peptidyl arginine deiminase 4 (PAD4), protein kinase Cβ1 (PKCβ1), phosphatylinositol 4 phosphate 5 kinase type II γ (PIP4K2C) and v raf murine sarcoma viral oncogene homologue B1 catalytic domain (BRAF)) that were recognised almost uniquely by sera from patients with RA on protein arrays. Using purified proteins, we confirmed that PAD4 and BRAF are recognised almost uniquely by patients with RA. Conclusion: We identified PAD4 and BRAF as RA specific autoantigens.